2014
DOI: 10.1159/000363244
|View full text |Cite
|
Sign up to set email alerts
|

Increased Density of <b><i>Demodex folliculorum</i></b> Mites in Pregnancies with Gestational Diabetes

Abstract: Objective: To investigate the presence of Demodex in patients with gestational diabetes and the impact of glucose regulation on Demodex density in gestational diabetes. Subjects and Methods: The study population consisted of 33 patients with gestational diabetes and 30 pregnant women without gestational diabetes (control group). The age, parity, gestational age, and BMI of the study group were recorded and the patients were divided into 2 groups, i.e. those with regulated and unregulated glucose levels, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The delicate host/ Demodex equilibrium may be tipped in favor of mite proliferation by various factors, including immunosuppression [ 61 88 ], diabetes [ 89 92 ]), vasodilatory-related factors [ 8 , 10 , 25 , 27 , 31 , 57 , 93 97 ], and/or sebaceous hyperplasia [ 8 , 10 , 51 , 98 ]. Initially, overproliferation of the mite is not clinically visible, giving rise to what could be called subclinical demodicosis, which can be observed in many skin conditions (including apparently healthy skin and any facial dermatosis), but is commonly encountered in ETR [ 97 ] (Fig.…”
Section: Demodex and Demodicosismentioning
confidence: 99%
“…The delicate host/ Demodex equilibrium may be tipped in favor of mite proliferation by various factors, including immunosuppression [ 61 88 ], diabetes [ 89 92 ]), vasodilatory-related factors [ 8 , 10 , 25 , 27 , 31 , 57 , 93 97 ], and/or sebaceous hyperplasia [ 8 , 10 , 51 , 98 ]. Initially, overproliferation of the mite is not clinically visible, giving rise to what could be called subclinical demodicosis, which can be observed in many skin conditions (including apparently healthy skin and any facial dermatosis), but is commonly encountered in ETR [ 97 ] (Fig.…”
Section: Demodex and Demodicosismentioning
confidence: 99%
“…Another study concludes that there was an increased Demodex density in gestational diabetes patients. This study stated that the reason for this result might be insufficient glucose regulation 30 …”
Section: Discussionmentioning
confidence: 80%
“…In a study that evaluated 42 patients with type 2 DM, DF was observed at a higher rate in the cases with diabetes (54.8%) (13). In a study of patients with gestational diabetes, the prevalence of DF was statistically significantly higher in the patients with gestational diabetes than in the normal pregnancies (24.2% vs 3.3%) (14). In our study, DF positivity was determined as 43.7% in DM patients.…”
Section: Discussionmentioning
confidence: 95%